TACKLING COVID-19 BASE ON THE CONCEPT OF TAGHYĪR (CHANGE) QS. AL-RA‘DU 11 - Rahmat Hidayat; Halimatussa’diyah Halimatussa’diyah (Program Studi Ilmu Al quran dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2022)
At the end of December 2019, people were shocked by the coronavirus disease-19. People believe that the virus spread from Wuhan, China. This epidemic finally attracted international attention, so that on January 30 WHO declared it a public health emergency. All humans worry over this situation. However, there are efforts to overcome it, one of which is by changing the psychological (inner) of the human being. This paper aims to review the concept of change (taghyīr) QS. al-Ra'du verse 11 in tackling covid-19. With a descriptive method of analysis literature review related to the topic this study resulted: QS. al-Ra'du verse 11 talks about social change (qaum) which starts from the mental condition (anfus) of the community. Changes that come from the community, concerning their inner side, are a prerequisite of changes by Allah. The inner side includes the mindset, strong determination, intention and understanding, so that from those create self-awareness. In any case, building awareness is the most important thing for achieving success and social change, especially in tackling Covid-19. People who are aware have to pay attention to their food and apply 3 M (wearing masks, washing hands with soap and keeping a distance).